Catholics and capital punishment: Do Pope Francis’s teachings matter in policy preferences? - Cullen, Francis T. (Punishment & society, 2022)
In the United States, Catholics make up more than 50 million members of the adult population, or about one in five Americans. It is unclear whether their religious affiliation shapes Catholics’ views on public policy issues, ranging from the legality of abortion to criminal justice practices. Capital punishment is especially salient, given that Pope Francis announced in 2018—as official Catholic Church teaching—that the death penalty is “inadmissible” under all circumstances. Based on two national surveys, the current project explores Catholics’ support for state executions before (2017) and after (2019) the Pope’s momentous change in the church’s Catechism. At present, little evidence exists that Pope Francis’s doctrinal reform has impacted Catholics, a majority of whom—like Americans generally—continue to favor the death penalty for murderers. Data from our additional 2020 MTurk survey show that only 17.0% of Catholic respondents could correctly identify the Church’s position on capital punishment. Despite these results, Pope Francis’s teachings provide Catholic leaders and activists with a compelling rationale for opposing the death penalty and holding Catholic public officials accountable for espousing offenders’ execution. Further, for the next generation of Catholics, instruction in the inadmissibility of capital punishment, as part of the Church’s consistent ethic of life, will be integral to their religious training.